The Current Situation of the Legislative Gap on Microplastics (MPs) as New Pollutants for the Environment - Casella, Claudio; Vadivel, Dhanalakshmi; Dondi, Daniele (Water, air, and soil pollution, 2024)
Microplastics (MPs) are plastic debris having a size ≤ 5 mm. The detrimental impact of MPs on the environment and, consequently, their dangerous effects on human health (emerging risk) have attracted much attention in recent years. Contamination by microplastics is difficult to measure, due to the non-standardization of collection, detection, and analysis techniques. This work consists of a bibliographic review of the analysis of the pros and cons of the various existing legislations at the international level, identifying the possible legislative gaps, intending to improve the efficiency of implementation of new policies on plastics and microplastics, offering the possible recommendations to address potential human and environmental health hazards caused by MPs pollution. Future studies on the mentioned subject should focus on a uniformity of methodology for the determination of microplastics and at the same time, offer help to governments, to write a legislative policy on plastics that is valid at the international level, to help the green earth and completely avoid the risk to human health.